The wave as a metaphor for the COVID-19 epidemic in the Polish press - Kołodziejczak, Małgorzata; Wrześniewska-Pietrzak, Marta (Papers in Linguistics, 2023)
The aim of the article is to determine how the wave metaphor functioned in press materials published in four newspapers: Rzeczpospolita, Gazeta Wyborcza, Super Express, and Fakt from April 1 to July 31, 2020. Additionally, it will focus on the image of the epidemic that is built using this metaphor. Analyses taking into account the cognitive perception of the metaphor showed that the wave in the analysed period not only served to explain and rationalize a new phenomenon, that is the coronavirus epidemic, but also facilitated a consistent presentation of both direct and secondary effects of the pandemic. It became a tool used by politicians who, by dotting their message with references to the wave metaphor, co-created an emotional message that was pejoratively charged. The image of the coronavirus built with the use of the wave metaphor present mainly in two periodicals – Gazeta Wyborcza and Rzeczpospolita – reinforced the image of the SARS-CoV-2 epidemic present in the media discourse as an enemy to be fought against.